Microwave Assisted Synthesis of Novel 1,2,3,4-Tetrahydrocarbazolyl thiazolidin-4-ones and Azetidin-2-ones and its Biological Behavior - T. Surendiran; S. Balasubramanian; Sivaraj D. (E-Journal of Chemistry)
A new family of 1,2,3,4 – tetrahydrocarbazolyl thiazolidin-4-ones (4a-e) and 1,2,3,4–tetrahydrocarbazolyl azetidin-2-ones (5a-e) were individually derived using N-[(α-substituted bezylidenehydrazino) acetyl] -1,2,3,4-tetra-hydrocarbazoles 3a-e by cyclization with thioglycolic acid and chloro- acetylchloride respectively. The compounds (3a-e) were prepared by condensation of N-(hydrazinoacetyl) 1,2,3,4-tetrahydrocarbazole (2) with a series of aldehydes. The compound 2 was obtained by the hydrazinolysis of N-(chloroacetyl)-1,2,3,4-tetrahydrocarbazole (1). These products were characterized by IR, NMR, MASS spectra and by elemental analysis. All the titled compounds (4a-e) and 5(a-e) were screened for antibacterial and antifungal activities.